MODELLING OF TEMPERATURE IN FULL-SCALE SYSTEMS: A REVIEW OF THE BIOLOGICAL HEAT GENERATION WITHIN WINDROW COMPOSTING - Stani, Abdil Halimis (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2012)
Sistem komposting windrow adalah metode yang umum digunakan untuk pengolahan limbah padat oraganik. Temperatur adalah variabel yang penting dalam pemodelan yang mana dapat disimulasikan dengan memperkirakan perubahan keseimbangan panas dari komponen pada setiap saat. Energi panas biologis adalah istilah yang paling signifikan dalam keseimbangan panas. Dalam tulisan ini pembangkitan panas oleh proses komposting diuji dan dievaluasi dalam penerapannya untuk sistem windrow skala penuh. Sampai saat ini keakuratan memprediksi laju degradasi substrat telah menjadi tantangan utama. Penggunaan pendekatan induktif berdasarkan ekspresi kinetik orde pertama ataupun relasi kinetik empiris telah ditemukan untuk tujuan praktis. Bagaimanapunjuga faktor skala koreksi untuk proses dan tipe substrat tertentu mungkin dibutuhkan investigasi lebih lanjut untuk perbedaan sempit diantara skala lab dan skala sistem skala penuh. Ã‚Â Kata kunci: Komposting terbuka, keseimbangan panas, panas biologis, model pengkomposanÃ‚Â AbstractWindrow composting is the most common method for organic solid waste treatment. Temperature is an important state variable in modelling, which could be simulated by estimating the change of heat balance components at any moment. Biological heat energy is the most significant term in the heat balance. In this paper biological heat generation of the composting process are examined and their applicability for a full-scale windrow system is evaluated. It is found that, to date, the accuracy of predicting the rate of substrate degradation has been a major challenge. The use of an inductive approach based on either first-order kinetic expression or empirical kinetics relation was found to be more feasible for practical purposes. However a scale-up correction factor for particular processes and types of substrate may need to be further investigated to narrow the discrepancies of kinetic performances between laboratory and full-scale systems.Ã‚Â Keywords: Windrow composting, Heat balance, Biological heat, Composting models